A novel OLT protection for hybrid WDM-TDM optical access networks - Kanungoe, Anirban; Das, Goutam (2014 IEEE International Conference on Advanced Networks and Telecommuncations Systems (ANTS), 2014)
In this paper a hybrid WDM/TDM based Optical Access Network architecture has been proposed that aims to provide optical line terminal (OLT) protection and partial feeder fiber protection without using any redundant OLT or any separate protection feeder fiber. An appropriate control mechanism to enable communication among the mutually supporting OLTs has also been introduced. The paper also presents a new procedure for calculating availability of service for providing shared OLT-protection. The availability of network service per end-user subject to different failure scenarios within the proposed network architecture has been explored. It was found that the proposed architecture provides significant cost benefits over previously proposed OLT protection schemes while achieving higher levels of network availability than most of the cases.